2010
DOI: 10.1155/2010/403830
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage in Lymphocytes of Copper Smelter Workers Correlated to Higher Levels of Excreted Arsenic

Abstract: Arsenic has been associated with multiple harmful effects at the cellular level. Indirectly these defects could be related to impairment of the integrity of the immune system, in particular in lymphoid population. To characterize the effect of Arsenic on redox status on this population, copper smelter workers and arsenic unexposed donors were recruited for this study. We analyzed urine samples and lymphocyte enriched fractions from donors to determinate arsenic levels and lymphocyte proliferation. Moreover, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 43 publications
3
10
0
Order By: Relevance
“…These findings concur with reports of elevated oxidative stress [27] and inflammation [21] in chronically-exposed adults. In a follow-up study ( n  = 44), As levels in maternal urine and placental and cord blood positively associated with cord blood 8-hydroxy-2'-deoxyguanosine and inversely associated with infant thymic function at birth, as measured by signal-joint T-cell receptor-rearrangement excision circles in cord blood mononuclear cells (CBMC) [80].…”
Section: Epidemiological Findingssupporting
confidence: 92%
“…These findings concur with reports of elevated oxidative stress [27] and inflammation [21] in chronically-exposed adults. In a follow-up study ( n  = 44), As levels in maternal urine and placental and cord blood positively associated with cord blood 8-hydroxy-2'-deoxyguanosine and inversely associated with infant thymic function at birth, as measured by signal-joint T-cell receptor-rearrangement excision circles in cord blood mononuclear cells (CBMC) [80].…”
Section: Epidemiological Findingssupporting
confidence: 92%
“…We found that LYM and NEUT counts showed different degrees of decline after ATO exposure, resulting in an increased percentage of LYMs and a decreased percentage of NEUTs. The reason for this is unclear but we speculate that human exposure to arsenic induces oxidative damage in LYMs [24]. Additionally, ATO exposure may cause immune inhibition in rats, leading to changes in the LYM and NEUT populations [25].…”
Section: Discussionmentioning
confidence: 90%
“…In addition to polluting the environment, heavy metals are known to induce adverse health effects in people living in polluted areas. Previous studies have reported smelters in Mexico ( 2 3 ), the United States of America ( 4 ), and Chile ( 5 ), giving off fumes containing sufficient arsenic (As), lead (Pb), and cadmium (Cd) to make long-term health management necessary for nearby residents.…”
Section: Introductionmentioning
confidence: 99%